2018
DOI: 10.17116/otorino201883162-64
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial anti-inflammatory photodynamic and light-emitting-diode phototherapy of the consequences of the gunshot and mine-blast injury to the face, head, and neck including damage to the ENT organs

Abstract: The objective of the present study was the enhancement of the effectiveness of the treatment of the consequences of the gunshot wounds and mine-blast injuries inflicted to the face, head, and neck encountered in the otolaryngological practice as well as the prevention of the formation of the large demarcation areas in the injured tissues and the preparation of these tissues for the further restorative treatment. Anti-microbial and anti-inflammatory photodynamic therapy (PDT) as well as light-emitting-diode (LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The use of PDT allowed to prevent the development of serious complications, reduce the number of drug therapies, and significantly reduce the duration of treatment. Studies have shown the high effectiveness of the proposed approach (143). In 2019 at the Sechenov University Oncology Center in Moscow, PDT treatment was conducted in patients with nonresectable bile duct carcinoma complicated by obstructive jaundice.…”
Section: Pdd and Pdt In Russia ñ Clinical Trials (Figure 14)mentioning
confidence: 99%
“…The use of PDT allowed to prevent the development of serious complications, reduce the number of drug therapies, and significantly reduce the duration of treatment. Studies have shown the high effectiveness of the proposed approach (143). In 2019 at the Sechenov University Oncology Center in Moscow, PDT treatment was conducted in patients with nonresectable bile duct carcinoma complicated by obstructive jaundice.…”
Section: Pdd and Pdt In Russia ñ Clinical Trials (Figure 14)mentioning
confidence: 99%